QAUL QODIM WA QAUL JADID IMAM SYAFI’I (KEMUNCULAN & REFLEKSINYA DI INDONESIA) - Khoirul Ahyar (Nizham Jurnal Studi Keislaman, 2015)
In this paper contains background of qaul qodim and qaul jadid. Where qaul qodim appeared in Iraq and qaul jadid in Egypt.Both qaul the results of thought of Imam Syafi'i. In his time, thought Syafi’i has evolved along with various backgrounds around. Initially, opinions or thoughts Syafi’i experience different impacts on the surrounding of social environment. But gradually, Imam Syafi'i thought it could be based on the usul fiqh. Even the book ar-treatise written by the Imam Syafi'i fiqh is considered as the basic premise of the law.Syafi’i great services for today can be felt, especially in Indonesia. Where there are many fatwas are set by the mufti and judge thanks to Imam Shafi'i contribute ideas. Qaul results of qaul jadid think do Syafi’i in egypt is the result of a refinement of thinking done in a long time. Egypt condition brought the contribution of his edea in the repertoire of new knowledge in an environment in various schools of thought. This is what makes that particular context will bring new experiences and views.